Interview with Professor Debra Bergoffen - Sapre Aude, Revista (Sapere Aude, 2013)
Interview with Professor Debra Bergoffen, Emerita Professor of Philosophy, George Mason University, USA; Bishop Hamilton Lecturer in Philosophy, American University, USA